Exploring the anticancer and antioxidant properties of Lagerstroemia speciosa bark extract via phytochemical and molecular docking analysis - Shahnaz Parvin Sweety; Tahsin Ahmed Rupok; Mst. Shahnaj Parvin; Jaytirmoy Barmon; Mst. Sarmina Yeasmin; Md. Ekramul Islam (Journal of Genetic Engineering and Biotechnology)
Lagerstroemia speciosa is traditionally used for treating diabetes and inflammation; however, its anticancer potential remains unexplored. This study assesses the antioxidant and anticancer activities of L. speciosa bark extract, with a focus on Ehrlich Ascites Carcinoma (EAC) cells in mice. The crude methanol extract (CME) was subdivided into n-hexane (NHF), chloroform (CHF), ethyl acetate (EAF), and aqueous (AQF) fractions. In vitro antioxidant assays identified CHF as the most active fraction, exhibiting high phenolic and flavonoid content. CHF and EAF were further investigated for anticancer activity in an EAC-induced mouse model, where CHF significantly (P < 0.05) reduced tumor cell count compared to EAF. Phytochemical characterization using FTIR and GC–MS revealed bioactive compounds, including 9-Methoxybicyclo[6.1.0]nona-2,4,6-triene and 9,12-Octadecadienoic acid methyl ester (E,E). Molecular docking studies demonstrated strong interactions between these compounds and key cancer-related proteins, p53 and Topoisomerase-II, suggesting potential anticancer mechanisms. Overall, this study shows that L. speciosa bark extract has therapeutic potential, especially for CHF. Bioactive compounds like 9,12-octadecadienoic acid methyl ester (E,E) and 9-methoxybicyclo [6.1.0]nona-2,4,6-triene contribute to the extract’s antioxidant and anticancer effects in EAC models, possibly by modulating p53 and Topoisomerase-II.